High-Intensity Interval Training vs. Plyometric EMOM: A Comparison of Effects on Body Composition and Physical Fitness in 18-19-Year-Old Karate Athletes - Rahmawan, Willy Adimas; Sumaryanto, Sumaryanto; Sumarjo, Sumarjo; Nevitaningrum, Nevitaningrum (Physical Education Theory and Methodology, 2026)
Background. A scientific contradiction exists in kumite preparation: HIIT (metabolic-dominant via AMPK/PGC-1α) and plyometric training (neuromuscular-dominant via SSC) are theoretically predicted to produce distinct adaptation patterns, yet empirical literature reports only isolated effects without explanatory models of adaptation transfer to karate-specific fitness demands. Objectives. This study aimed to compare the effects of conventional High-Intensity Interval Training (HIIT) and plyometric training using the Every Minute on the Minute (EMOM) format on physical fitness and body composition in male karate athletes aged 18-19 years. Materials and Methods. Forty-four male karate athletes (aged 18-19 years) from the Polda DIY Karate Club were assigned to a quasi-experimental two-group pretest-posttest design, completing HIIT (n = 22) and plyometric-EMOM (n = 22) training over 8 weeks. Physical fitness was assessed using the Indonesian Physical Fitness Test (TKJI); body composition was measured using a Tanita BC-545N. Results. Both groups improved substantially (p < 0.001). Significant Time×Group interactions were observed for TKJI, body fat, and body weight (all p < 0.001), with a moderate interaction for FFM (p = 0.028). The HIIT group demonstrated greater TKJI gains (Δ = +3.09 vs. +0.95), while the plyometric-EMOM group produced greater fat loss (Δ = −5.36% vs. −4.29%). Extremely large effect sizes (Cohen’s d up to 6.80) reflect low variance within a homogeneous single-club sample rather than universal biological effects. Conclusions. HIIT is superior for physical fitness via metabolic-cardiovascular pathways, whereas plyometric-EMOM excels in fat reduction via SSC-driven eccentric energetics, confirming the Dual-Pathway Specificity Model. These findings are context-specific to elite junior male karate athletes and require further validation for broader generalization.